Alcohol Expectancies Mediate and Moderate the Associations between Big Five Personality Traits and Adolescent Alcohol Consumption and Alcohol-Related Problems - Ibáñez, Manuel I.; Camacho, Laura; Mezquita, Laura; Villa, Helena; Moya-Higueras, Jorge; Ortet, Generós (Frontiers in Psychology, 2015)
Personality and expectancies are relevant psychological factors for the development of adolescent alcohol use and misuse. The present study examined their direct, mediation and moderation effects on different drinking behaviors in adolescence. Personality domains of the Five-Factor Model, positive and negative alcohol expectancies, alcohol use during the week and at the weekend, and alcohol-related problems were assessed in a sample of 361 adolescents. Different personality dimensions were directly associated with specific alcohol outcomes: Extraversion, low Conscientiousness and low Openness were associated with weekend alcohol use; low Agreeableness was related to weekday use; whereas low Agreeableness, low Conscientiousness and Extraversion were associated with alcohol-related problems. In addition, positive alcohol expectancies mediated the relationship between Extraversion and alcohol use, whereas both positive and negative expectancies mediated between Neuroticism and alcohol consumption and alcohol-related problems. Finally, both types of expectancies interacted with Extraversion to predict alcohol problems. Our results highlight the importance of examining the complex interplay of comprehensive personality models and alcohol expectancies to gain a better understanding of the development of different alcohol use and misuse patterns in adolescence.